Empowering Reproductive Age Women through Interactive Modern Contraception Education for Healthy Families at Puskesmas Segiri, Samarinda - Febriana Metallica Yeng Heling; Gunarmi; Indah Purnamasari (Indonesian Health Issue, 2026)
Background: Limited knowledge among Women of Reproductive Age (WRA) regarding modern contraception remains a challenge in the Family Planning program. Objective: This study aimed to improve WRA understanding of modern contraceptive methods through an interactive digital media-based educational approach. Methods: This community-based intervention employed an educational design involving 28 WRA in the working area of Puskesmas Segiri, Samarinda. Data collection was conducted using educational counseling supported by interactive video and a digital pocketbook, followed by pre-test and post-test assessments to measure knowledge changes. The activity was implemented through preparation, implementation, and evaluation phases, and data were analyzed descriptively using mean, percentage, and standard deviation comparisons. Results: The findings revealed a significant improvement in participant knowledge, with the proportion of good knowledge increasing from 61% during the pre-test to 100% in the post-test. The mean score increased from 85.00 to 97.14, while the standard deviation decreased from 15.396 to 3.951, showing improved consistency in participant understanding. The digital pocketbook also proved effective as a sustainable educational medium that participants could access repeatedly. Conclusion: Interactive digital education is highly effective in improving contraceptive knowledge among WRA and is recommended for replication in other regions with similar characteristics to support sustainable family planning education.